Revision of the Afrotropical species of the genus Anterhynchium de Saussure (Hymenoptera: Vespidae: Eumeninae) - Selis, Marco; Carpenter, James M. (Zootaxa, 2023)
A taxonomic study on the Afrotropical species in the genus Anterhynchium de Saussure, 1863 is presented. Some subspecies are elevated to specific rank (Anterhynchium argenteopilosellum (Giordani Soika, 1937) stat. nov., A. bugandanum Giordani Soika, 1987 stat. nov., A. cariosum Giordani Soika, 1987 stat. nov., A. denticulatum (Mocsáry, 1903) stat. nov., A. sulphureomaculatum (von Schulthess, 1928) stat. nov.). New synonymies are proposed for Anterhynchium fallax (de Saussure, 1852) (=Rhynchium luctuosum Gerstäcker 1857 syn. nov.), Anterhynchium grandidieri (de Saussure, 1890) (= Epiodynerus grandidieri limbatulus Giordani Soika, 1991 syn. nov.), Anterhynchium grayi (de Saussure, 1855) (= Synagris inermis var. atrata Mocsáry, 1903 syn. nov.; = Rhynchium grayi var. sumptuosum Gribodo, 1895 syn. nov.), Anterhynchium mephisto (Gribodo, 1892) (= Anterhynchium beninum Gusenleitner, 2018 syn. nov.; = Odynerus rufoniger Bequaert, 1918 syn. nov.; = Synagris uncata Tullgren, 1904 syn. nov.); Anterhynchium synagroide (de Saussure, 1852) (=Rhynchium synagroides var. alpha von Schulthess, 1923 syn. nov.; Rhynchium synagroides var. beta von Schulthess, 1923 syn. nov.), Anterhynchium andreanum (de Saussure, 1890) (= Odynerus andreanus discolor Giordani Soika, 1941 syn. nov.); Anterhynchium synagroide gamma (von Schulthess, 1924) is considered as a doubtful synonym of A. argenteopilosellum syn. nov. The nominal subgenus is redefined and divided into the following species-groups: grayi species-group, mephisto species-group, osborni species-group and synagroide species-group. The Malagasy species are transferred from Epiodynerus Giordani Soika to the nominal subgenus but considered as incertae sedis in it. Odynerus natalensis de Saussure, 1855 and Anterhynchium uniforme Gusenleitner, 2012 are transferred to Antodynerus de Saussure, 1855 (Antodynerus natalensis comb. nov. and Antodynerus uniforme comb. nov.), Rhynchium histrionicum Gerstäcker, 1857 is transferred to Euodynerus Dalla Torre, 1904 (Euodynerus (Euodynerus) histrionicus comb. nov.), Rhynchium holomelas André, 1895 is transferred to Pseudagris de Saussure, 1863 (Pseudagris holomelas comb. nov.; = Rhynchium junodianum von Schulthess, 1899 syn. nov.; = Synagris aterrima Maidl, 1914 syn. nov.), Anterhynchium obscurum Gusenleitner, 2007 is transferred to Tricarinodynerus Giordani Soika, 1952 (Tricarinodynerus obscurus comb. nov.). Anterhynchium dahomeyicus Gusenleitner, 2018 is a junior synonym of Aethiopicodynerus punctiventris (Gusenleitner, 2002) syn. nov. Lectotypes for Odynerus andreanus de Saussure, 1890 and Rhynchium sulphureomaculatum von Schulthess, 1928 are designated. A key to the species is provided.